Transcatheter Closure of Patent Ductus Arteriosus in Infants With Weight Under 1,500 Grams - Fraisse, Alain; Bautista-Rodriguez, Carles; Burmester, Margarita; Lane, Mary; Singh, Yogen (Frontiers in Pediatrics, 2020)
Persistent patent ductus arteriosus (PDA) is very common in preterm infants, especially in extremely preterm infants. Despite significant advances in management of these vulnerable infants, there has been no consensus on management of PDA – when should we treat, who should we treat, how should we treat and in fact there is no agreement on how we should define a hemodynamically significant PDA (often referred as large PDA needing intervention). Medical management with non-steroidal anti-inflammatory drugs (NSAIDs) remains the first line of therapy but they are associated with significant adverse effects and moderate success rate in closing the PDA. The results of paracetamol use for the closure of PDA in extremely preterm infants are not very successful in the clinical practice, although they were reported to be encouraging in the preliminary published studies. Surgical ligation of PDA is not without significant increase in mortality and co-morbidities. Recently, there has been a significant interest in percutaneous transcatheter closure of PDA in preterm infants, including extremely preterm infants. Percutaneous closure of PDA in premature babies can be achieved with a high degree of success as an alternative to surgical ligation. Early and mid-term follow-up confirms promising results. Future efforts should be aimed at optimizing patient selection and timing of the procedure. Further studies are needed to assess the results and outcomes of this technique versus current treatment strategies including medical treatment.